Inexperienced water users can "Float to Live" in realistic open water conditions - Clare Eglin; Heather Massey; Geoff Long; Adrian Mayhew; Michael Tipton (BMC, 2024)
Abstract Background The RNLI "Float to Live" campaign is based on research conducted in indoor pools with experienced open water swimmers. Study 1 investigated whether the RNLI "Float to Live" guidance would enable less experienced individuals to float in realistic open water conditions. Study 2 examined the separate effects of practice and coaching on floating competence. Methods Study 1: Inexperienced water users conducted floats in either still, open fresh (n = 22) or open sea water (n = 13), followed by moving sea (n = 6) or fresh water (n = 5). Participants undertook three 2-min floats in still water wearing swimwear and one clothed float: 1) naïve; 2) following RNLI "Float to live" messaging; 3) individual float coaching; 4) simulated fall wearing summer clothing. In moving sea water, participants undertook two floats equivalent to Floats 3 and 4. In moving fresh water, participants undertook 3 floats: 1) naïve; 2) following "defensive floating" coaching; 3) simulated fall wearing summer clothing. Study 2: Two groups matched for skinfold thickness undertook three 2-min floats in a flume wearing swimwear. PRAC group (n = 12): 1) naïve; 2) following float practice; 3) float coaching; COACH group (n = 11) coaching followed by practice. Floating difficulty, confidence, competence, "efficiency" and perceived exertion were analysed using either a Friedman test or mixed model ANOVA. Results In both fresh water and sea water, participants' floating competence and confidence increased after viewing the RNLI messaging, it was further improved with individualised float coaching. The additional helpful instructions included: 1) "head back with ears submerged"; 2) "relax"; 3) "breathe normally"; 4) "it is OK if your legs sink"; 5) an accurate description of sculling for "active" floaters that needed it; 6) spread arms and legs for stability. The simulated fall with clothing did not impair floating competence. No difference in floating competence was seen between PRAC and COACH, though confidence may be increased sooner in COACH. Conclusions The RNLI float advice can be applied in realistic open water settings by less experienced water users. Additional content could be included to make the messaging even more effective.